CRISPR-Cas9 Toolkit for Genome Editing in an Autotrophic CO2-Fixing Methanogenic Archaeon - Jie Li; Liuyang Zhang; Qing Xu; Wenting Zhang; Zhihua Li; Lei Chen; Xiuzhu Dong (Microbiology Spectrum, 2022)
ABSTRACT The CRISPR-Cas9 system is a robust genome editing tool that is widely applied in eukaryotes and bacteria. However, use of this technique has only been developed for one species of Archaea, a domain of life ranking in parallel with Eukarya and Bacteria. In this study, we applied the CRISPR-Cas9 genome editing technique to Methanococcus maripaludis, an autotrophic and hydrogenotrophic methanogenic archaeon with a remarkably polyploid genome comprising up to ~55 chromosomal copies per cell. An editing plasmid was designed that encodes small guide RNA (sgRNA), Cas9 protein and an ~1-kb repair template (donor). Highly efficient (75% to 100%) and precise genome editing was achieved following one-step transformation. Significantly, the Cas9-based system efficiently deleted one or two genes and a large DNA fragment (~9 kb) and even synchronously deleted 13 genes located at three loci in all chromosomal copies of M. maripaludis. Moreover, precise in situ genome modifications, such as gene tagging and multiple- and even single-nucleotide mutagenesis, were also introduced with high efficiency. Further, as a proof of concept, precise mutagenesis at the nucleotide level allowed the engineering of both transcriptional and translational activities. Mutations were introduced into an archaeal promoter BRE (transcription factor B [TFB] recognition element), a terminator U-tract region, and a gene coding region. Stop codon introduction into a gene through single-nucleotide substitution shut down its expression, providing an alternative strategy for gene inactivation. In conclusion, the robust CRISPR-Cas9 genetic toolkit developed in this investigation greatly facilitates the application of M. maripaludis as a model system in the study of archaeal biology and biotechnology development, particularly CO2-based biotechnologies. IMPORTANCE Archaea are prokaryotes with intriguing biological characteristics. They possess bacterial cell structures but eukaryotic homologous information processing machinery and eukaryotic featured proteins. Archaea also display excellent adaptability to extreme environments and play pivotal roles in ecological processes, thus exhibiting valuable biotechnological potential. However, the in-depth understanding and practical application of archaea are much lagging, because only a minority of pure cultures are available, and even worse, very few can be genetically manipulated. This work developed CRISPR-Cas9-based genome editing technology in Methanococcus maripaludis, a CO2-fixing methanogenic archaeon. The CRISPR-Cas9 approach developed in this study provides an elegant and efficient genome editing toolkit that can be applied in the knockout of single or multiple genes, in situ gene tagging, multiple- or single-nucleotide mutagenesis, and inactivation of gene expression by introduction of stop codons. The successful development of the CRISPR-Cas9 toolkit will facilitate the application of M. maripaludis in archaeal biology research and biotechnology development, particularly CO2-derived biotechnologies.